Identités nationales, identités « raciales » en Océanie - Adrien Rodd (Revue Française de Civilisation Britannique)
Discourses and politics in the Pacific, as in other regions of the world, have at times equated ‘race’ and nation as a basis for statements on national identity. The objective of this article is to analyse the ways in which the requirement for national unity has been grounded, in that region, on the perception or promotion not just of a cultural homogeneity, but also an ethnic or ‘racial’ one, sometimes reinforced by policies to exclude minorities. In Australia and New Zealand, the current promotion of cultural diversity by the governments contrasts with a long-lasting, earlier bipartisan agreement on the preservation of exclusively ‘White’ and ‘British’ nations. In the Pacific islands, state-endorsed discrimination has been rare since independence –despite counter-examples in Fiji and Nauru, two countries with sizeable minorities of foreign descent–, but the self-image of these nations rests upon that of a homogenous indigenous ethnicity and culture, wherein minorities appear permanently ‘foreign’. In addition, persons of Chinese origin, part of an increasingly visible minority, have been subject to rejection, and even to racially motivated violence, in several island countries in recent years – as though in echo to a similar violence which once marked Australia. This study focuses on the place granted to minorities in Pacific countries, divided between nations certain of their homogenous identity, and those attempting to build a still uncertain form of multicultural national identity.